Real‐Time PEGDA‐Based Microgel Generation and Encapsulation in Microdroplets. Issue 2 (12th May 2016) - Martino, Chiara; Vigolo, Daniele; Solvas, Xavier Casadevall i; Stavrakis, Stavros; deMello, Andrew J.
Abstract : Herein, a method is reported that combines droplet‐based microfluidics and microscope projection photolithography for the generation of poly ethylene glycol diacrylate microgels and their encapsulation within pL‐volume droplets. By implementing continuous‐flow photolithography in the vicinity of a cross junction, the real‐time generation and in situ encapsulation of fiber‐like structures within pL‐volume aqueous microdroplets is demonstrated. The effect of UV excitation is assessed at varying distances from the cross junction for both constant and pulsed UV excitation modes, as a route to controlling microfiber length. Finally, UV excitation within trapped droplets is explored and how the combination of the two techniques can lead to the generation of 3D patterned microstructures is demonstrated, opening new avenues for the rapid generation of inner scaffolding of artificial cell facsimiles. Abstract : The feasibility of combining droplet‐based microfluidics with projection photolithography is demonstrated. Using both running and trapped droplets PEGDA microstructures are generated and their geometries are tuned. It is predicted that these structures can find application in tissue engineering, droplet‐based bioassay and artificial cell studies.